Effectiveness of Sandalwood Aromatherapy on Sleep Quality in Elderly Patients with Hypertension: A Gerontological Nursing Case Study at Wanaseraya Social Care Home - Ni Komang Matalia Gandari; Komang Ayu Widiatrini; I Made Rismawan; Ni Putu Cyntia Maseni (PT BMW Journal Sejahtera, 2026)
Background: Hypertension is a major public health concern associated with increased risks of cerebrovascular and cardiovascular disease. Elderly patients with hypertension often experience poor sleep quality, which further aggravates their condition. Non-pharmacological interventions, such as aromatherapy, are increasingly recognized as effective adjuncts for improving sleep quality. Objective: This study examined the effectiveness of sandalwood aromatherapy as a non-pharmacological nursing intervention to improve sleep quality among elderly patients with hypertension residing at Wanaseraya Social Care Home, Denpasar, Bali. Methods: A qualitative case study design was employed involving three elderly patients (aged 62–65 years) with hypertension and documented sleep disturbances. The intervention consisted of sandalwood aromatherapy administered via electric vaporizer for 30 minutes nightly over three consecutive nights. Sleep quality was assessed using the Pittsburgh Sleep Quality Index (PSQI) at baseline and post-intervention. Nursing care was documented in accordance with Indonesian Nursing Standards (SDKI, SIKI, SLKI). Results: All three patients demonstrated measurable improvement in sleep quality. PSQI scores decreased from poor (6–7) to good (5) following three sessions of aromatherapy. Subjective reports indicated reduced nocturnal awakenings, faster sleep onset, and greater overall satisfaction with sleep. Conclusion: Sandalwood aromatherapy delivered via electric vaporizer is an effective, safe, and practical non-pharmacological intervention for reducing sleep disturbances in elderly hypertensive patients. Incorporating this approach into routine gerontological nursing care at social care homes is recommended.